The research of the level of the formation of knowledge, skills and attainments in sport tourism of the students of the physical education faculty - Соколова [Sokolova O.], Ольга Валентинівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]-->The results of the estimation of the level of the formation of knowledge, skills and attainments in sport tourism of the students of the physical education faculty of the Zaporyzhyan National University are presented. The students of the 3rd year of study of such educational direction as «Physical education», «Human`s health» and «Sport» took part in the research. The data of the interviews with the students, questionnaire interviews with the teachers of the physical culture at comprehensive schools in Zaporizhzha are also used in the research in order to find out the level of the proficiency of attainments in sport tourism organization of the school year old children. The results of the interviews with the teachers of the faculty also served as the data for the research on the base of which the proficiency of knowledge, skills and attainments in sport tourism of the students are found out. It is established, that the level of the main part of the attainments in sport tourism organization and carrying out of the students may be evaluated as satisfactory<!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->